Mediação popular: o direito fundamental do acesso à justiça como prática emancipatória - Almeida, Ana Lia Vanderlei de (2009)
Mediation is an Alternative Dispute Resolution (ADR) that is becoming increazingly important Brazil, in which a neutral third party facilitates the parties' own settlement process. The present research reflects about this mechanism's political potential, based on a community mediation experience (internship at Juspopuli human right organization — Salvador-BA). There are four fundamental points in our research. The first one is about mediation itself: what people commonly think about it and where are the critical reflections about its usage directed to. The second one is the conflict: how we experience it in our culture, which elements need to be reflected upon so that the role of conflict can be changed in our society and community mediation as a builder of a dialogue culture. The third one is the right: the defining elements of the traditional comprehension of the juridical phenomenon, with its reduction to the law, an other possible paradigms in the field of critical theories of law which are meant to support community mediation practices. Finally, the parties: the prevailing idea we have about them and a critical panorama to encourage autonomy and respect for the other in the construction of new forms of subjectivity through community mediation.